Successful implementation of erosion and sedimentation control plan for reducing environmental impact in the construction industry - Asri Syahmi, Asnor (2022)
Human-made erosion and sedimentation can severely affect the environment. Environmental protection plans, including the erosion and sedimentation control plan (ESCP), can reduce construction sites' environmental impacts. However, numerous challenges are hindering successful ESCP implementation. This study shows support for the United Nations Sustainable Development Goals. This study is done towards the 11th goal, 11.C, sustainable cities and communities. SDG 11's official mission is to "Make cities inclusive, safe, resilient and sustainable" (Assembly, U. G., 2017). While understanding the underlying challenges in ESCP implementation can address that problem, that information is lacking. This study investigates the factors for implementing ESCP successfully in developing countries such as Malaysia by determining the key challenges for implementing ESCP, identifying the critical success factors for implementing ESCP, and classifying the relationship between the identified critical factors. The target population for the interviews is individual professionals that are involved in ESCP implementation, including officers from the Department of Environment, the Department of Irrigation and Drainage, and Infrastructure Department of City Halls, City Councils, Municipal Councils, and District Councils, Engineers and Environmental officers of contractors and consultant firms. This research uses a questionnaire survey as the methodology to answer the research objective. Therefore, this study identifies the key challenges in implementing ESCP at construction sites. To achieve that objective, data from the 102 participants in the key challenges in implementing ESCP surveys undergo the descriptive analysis to find the mean and standard deviation before the normalized value is calculated. The normalized value indicates the success factor is critical, and the success factor is important when normalized is above 0.50. Then, from the normalized value, the overall data is listed. Factor analysis minimizes the number of variables at each factor with large loads and groups them into several groups of a component. Finally, the list of components for both research objectives is listed. Key challenges in implementing ESCP can be categorized into three components: knowledge, attitude and awareness, technical issue, and cost. Solving these challenges may increase the implementation of ESCP. Thus, it will save our environment while building our nation. At the same time, critical success factors in implementing ESCP can be categorized into four components: Enforcement, Knowledge, Attitude and Awareness, Management, and Planning. Implementing these factors may result in an increase in the implementation of ESCP in our construction industry. Thus, Malaysia can develop while maintaining its natural treasures for our future generations. Last but not least, this paper helps create awareness, knowledge, and importance of ESCP helps to manage their resource allocation properly, assisting industry practitioners to develop strategies that target to eliminate the less effective method that is currently used to improves the success rate of implementing ESCP, adding new literature in current literature, and support government authorities in policymaking to decide between tackling problems related to the implementing of ESCP. The major findings include the key challenges for implementing ESCP are: ‘progress between ESCP and construction works is not parallel,’ ‘lack of publicity on ESCP,’ ‘failure to maintain ESCP facilities periodically,’ ‘cost-reduction process in ESCP implementation,’ ‘contractors perceived that ESCP is overcharged,’ and ‘completed the ESCP just for the report.’ Also, the fragmentation between project stakeholders in the construction industry results in other key challenges that partially affect some project members. These findings contribute a better knowledge in developing strategies for effective ESCP implementation to protect the environment.